Comparative phylogeography of two sister species of snowcock: impacts of species-specific altitude preference and life history - Bei An; Lixun Zhang; Yutao Wang; Sen Song (Avian Research, 2020)
Abstract Background Phylogeographical patterns and population dynamics are usually interpreted by environmental disturbances and geographic barriers of the past. However, sister species may exhibit disparate patterns of genetic structures and population dynamics due to their habitat preference and altitude segregation. In this study, we tested how species-specific altitude habitat affected phylogeographical patterns in two sister snowcock species, Tibetan (Tetraogallus tibetanus) and Himalayan Snowcocks (T. himalayensis). Methods A panel of seven microsatellite loci and a fragment of Mitochondrial DNA Control Region were used to investigate genetic structures and population dynamics in hope of revealing the underlying evolutionary processes through the identification of possible past demographic events. Results Our results suggest that T. himalayensis showed a significant phylogeographical signal in mtDNA (F ST = 0.66, p < 0.001) and microsatellite (F ST = 0.11, p < 0.001) data and is stable during the glacial-interglacial cycles in the Pleistocene and followed demographic contraction until 0.003 million years (Mys) ago. The phylogeographical signal of T. tibetanus is lower than the level of genetic difference among populations in mtDNA (F ST = 0.41, p < 0.001) and microsatellite (F ST = 0.09, p < 0.001) data, likely benefiting from stable habitats over a long period of time. T. tibetanus has been experiencing expansion since 0.09 Mys ago. However, an abnormally haplotype H9 from T. himalayensis clustering with T. tibetanus was spotted. Conclusion Our results indicate that differences in habitat preference and altitude specialities were reflected in the genetic structure patterns and population dynamics of these two species. These dissimilarities in life history traits might have affected the dispersal and survival abilities of these two species differently during environmental fluctuations. The results of this study also enriched our knowledge on population differentiation and connectivity in high altitude mountain ecosystems.